2016
DOI: 10.2131/jts.41.65
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of poisonous mushrooms using nuclear ITS region and peptide toxins: a retrospective study on fatal cases in Thailand

Abstract: Cases of mushroom poisoning in Thailand have increased annually. During 2008 to 2014, the cases reported to the National Institute of Health included 57 deaths; at least 15 died after ingestion of amanitas, the most common lethal wild mushrooms inhabited. Hence, the aims of this study were to identify mushroom samples from nine clinically reported cases during the 7-year study period based on nuclear ITS sequence data and diagnose lethal peptide toxins using a reversed phase LC-MS method. Nucleotide similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 19 publications
(19 reference statements)
0
30
0
Order By: Relevance
“…For the identification of medicinal plants, the internal transcribed spacer 2 (ITS2) sequence combined with the psb A- trn H sequence was recommended as one of most suitable DNA barcode [ 19 , 20 ], and ITS2 was used to accurately distinguish medicinal plants in Artemisia [ 21 ]. Nuclear ITS sequence data can also be utilized to provide new information for identifying poisonous mushroom species [ 22 ] and to study the genetic diversity of M . albus and M .…”
Section: Introductionmentioning
confidence: 99%
“…For the identification of medicinal plants, the internal transcribed spacer 2 (ITS2) sequence combined with the psb A- trn H sequence was recommended as one of most suitable DNA barcode [ 19 , 20 ], and ITS2 was used to accurately distinguish medicinal plants in Artemisia [ 21 ]. Nuclear ITS sequence data can also be utilized to provide new information for identifying poisonous mushroom species [ 22 ] and to study the genetic diversity of M . albus and M .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular identification of a wild fungal sample is important to determine the species of the sample [22]. Thus, molecular identification was performed on wild G. lucidum .…”
Section: Resultsmentioning
confidence: 99%
“…BLAST analysis confirmed that the genomic DNA isolated from the collected mushroom labeled as SAMPLE_K002 was a fungal nrDNA, which showed 99.76% similarity to the GenBank nucleotide sequence of C. molybdites (KP012712.1). Phylogenetic analysis further confirmed that among nine related nucleotide sequence, sequence of SAMPLE_K002 was found homologous to C. molybdites with 72 % bootstrap support [ Similarly, using BLAST sequence analysis of the ITS region, Parnmen et al [21] confirmed the molecular identity of poisonous mushrooms in Thailand with similarities ranging from 88% to 100%. In addition, Reyes et al [8] reported the molecular identity of two newly recorded Termitomyces species in the Philippines, the T. bulborhizus and T. clypeatus with similarities of 92% and 87%, respectively.…”
Section: Molecular Identification Of Mushroommentioning
confidence: 79%